The Economic Impact of The Implementation of The Lucky Waste Program in the Oyster Mushroom Cultivation Farmer Group of Payakabung Village, North Indralaya Sub-District, Ogan Ilir District - Husein, Saddam; Heryanto, Abdul Roni; Prayogo, Kurniawan Bagus Dwi; Hadjri, Muhammad Ichsan (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to determine and analyze the economic impact of the implementation of the Bertuah Waste Program in the Oyster Mushroom Farmer Group of Payakabung Village, North Indralaya District, Ogan Ilir Regency. The Bertuah Waste Program is a flagship Corporate Social Responsibility (CSR) program of PT PLN Indonesia Power UBP Keramasan UP Indralaya. This program aims to have an impact on improving the community's economy and as a form of effort to overcome environmental problems around Payakabung Village, such as the generation of palm frond waste which is a factor in the severe condition of forest and land fires, as well as the generation of baglog waste which is used as liquid smoke. The method used in this research is a qualitative approach with a descriptive method. The results showed that the Bertuah Waste Program is a form of development and innovation from oyster mushroom cultivation activities in Payakabung Village which has been running since 2022. The Bertuah Waste Program has shown impacts, both in terms of economy and environment for the community, especially members of the Oyster Mushroom Farmer Group and Srikandi Payakabung. The economic impact is shown in the form of savings in raw material costs, savings in vegetable pesticide costs, and increased income for group members.